Synthesis, characterization and electrical properties of N-([4-(aminophenylethynyl)toluene]-N’-(cinnamoyl)thiourea (AECT) as single molecular conductive film - Wan M. Khairul; Nizamuddin Tukimin; Rafizah Rahamathullah (Penerbit Universiti Kebangsaan Malaysia, 2016)
The exploitation of mixed moieties of conjugated acetylide and thiourea system as molecular wire candidates surprisingly unexplored in this distinctive area although the well-known rigid π-systems enhance the electronic field at some extend. Therefore, in the present research, interest has been focused on the design, synthesis, fabrication and evaluation of the performance of a new acetylide-thiourea, N-([4-(aminophenylethynyl)toluene]-N’-(cinnamoyl)thiourea (AECT) based on Donor (D)-π-Acceptor (A) system as an active layer in conductive film. The compounds were successfully characterized via infrared spectroscopy (IR), UV-visible absorption spectroscopy (UV-Vis), CHNS elemental analysis, 1H and 13C nuclear magnetic resonance spectroscopy (NMR), thermogravimetric analysis (TGA) as well as cyclic voltammetry (CV) analysis. The investigation of its potential as dopant system in conductive film was fabricated on ITO substrate prior to the evaluation of its conductivity properties which was carried out by Four Point Probe. The findings from the conductivity analysis showed that the prepared film, AECT/ITO performed better and exhibited increasing conductivity up to 0.2044 Scm-1 under maximum light intensity of 150 Wm-2. This proposed molecular framework gives an ideal indication to act as conductive film and has opened wide potential for application in organic electronic devices.